Chine, Japon, ASEAN : compétition stratégique ou coopération? - Godement, François; Boisseau du Rocher, Sophie; Crombé, Xavier; Serra, Régine (Paris : IFRI, 1999)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: samenwerking; China; Japan